2005
DOI: 10.1016/j.csr.2004.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of warm water intrusions on populations of macrozooplankton on Georges Bank, Northwest Atlantic

Abstract: As part of the Georges Bank/North West Atlantic GLOBEC (Global Ocean Ecosystems Dynamics) Program, macrozooplankton and micronekton were collected on 30Broad Scale Survey Cruises between January -June, 1995-1999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…if there is a self-sustaining, reproducing population. Neomysis americana occurs in the North Atlantic from 468N along Canadian and USA coastal waters (Hulburt, 1957;Herman, 1963;Williams, 1972;Williams et al, 1974;Prouse, 1986;Brown et al, 2005), but it is not reported for Central America or northern South American waters. It was first cited for South America in Montevideo Harbour, Uruguay (358S: González, 1974), and since then it has been found in other Uruguayan sites (Calliari et al, 2001(Calliari et al, , 2007Rodriguez-Graña et al, 2008), in southern Brazil (Tramandaí and Lagoa dos Patos, 308-328S: Tavares & Bond-Buckup, 1990; Gama, 2008) south-west atlantic mysids geographical distribution and Argentina (368 -408S, Hoffmeyer, 1990;Viñas et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…if there is a self-sustaining, reproducing population. Neomysis americana occurs in the North Atlantic from 468N along Canadian and USA coastal waters (Hulburt, 1957;Herman, 1963;Williams, 1972;Williams et al, 1974;Prouse, 1986;Brown et al, 2005), but it is not reported for Central America or northern South American waters. It was first cited for South America in Montevideo Harbour, Uruguay (358S: González, 1974), and since then it has been found in other Uruguayan sites (Calliari et al, 2001(Calliari et al, , 2007Rodriguez-Graña et al, 2008), in southern Brazil (Tramandaí and Lagoa dos Patos, 308-328S: Tavares & Bond-Buckup, 1990; Gama, 2008) south-west atlantic mysids geographical distribution and Argentina (368 -408S, Hoffmeyer, 1990;Viñas et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…North American Atlantic coast (Hulburt, 1957;Herman, 1963;Wigley & Burns, 1971;Williams, 1972;Williams et al, 1974;Zagursky & Feller, 1985;Prouse, 1986;Brown et al, 2005;Taylor et al, 2005; and references therein; authors' own unpublished data); and Holland (Wittmann et al, 2012).…”
Section: Othersmentioning
confidence: 94%
“…The co-occurrence of Phronima and Salpa spp. in the Georges Bank, Northwest Atlantic is well known (Brown et al 2005).…”
Section: Relation Between Hyperiid Amphipods and Salpsmentioning
confidence: 99%
“…Additionally, the warm water intrusions in 1995 could have advected slope water predators onto Georges Bank (Brown et al 2005), thereby increasing overall predation rates, as well as rates on the flank.…”
Section: Predationmentioning
confidence: 99%
“…Many of the invertebrate predators were sampled during the GLOBEC GB study with a 10 m 2 MOCNESS (Brown et al 2005). First, the fraction of tows found containing each predatory taxon was used to test if there was a significant difference in the presence of each taxon between years.…”
Section: Predationmentioning
confidence: 99%